Toeplitz Determinants for the Class of Functions with Bounded Turning (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we obtain the upper bounds of the Toeplitz determinants for the class of functions with bounded turning. We also present some consequences of our main results. Some estimates obtained on Toeplitz determinants are sharp.
Keywords: Bounded turning function; Toeplitz determinants; Univalent function